Factors Influencing Employee Productivity (Case Study of the Craft Industry of MSMEs in Yogyakarta City, Special Region of Yogyakarta Province) - FX. Pudjo Wibowo; Eso Hernawan; Gregorius Widiyanto (LPPM Universitas Buddhi Dharma, 2026)
The purpose of this study was to use a simple random sampling method to distribute questionnaires to employees of MSMEs in Yogyakarta City, Yogyakarta Special Region, to determine the influence of work, promotions, coworkers, superiors, and the work environment on employee productivity. Work, promotions, coworkers, superiors, and the work environment are independent factors in this study, while employee productivity in the MSME craft industry in Yogyakarta City is the dependent variable. We conducted a survey of employees of micro, small, and medium enterprises (MSMEs) in Yogyakarta City, Yogyakarta Special Region, by sending questionnaires directly to them. Using SPSS Version 25.00 and employee data from Yogyakarta City, Yogyakarta Special Region, this study employed multiple regression analysis, coefficient of determination analysis, F-test, and t-test. The adjusted R2 value in this study indicates that 78.1% of the variance in employee productivity can be explained by work, promotions, coworkers, superiors, and the work environment through the model, with the remaining 21.9% coming from other variables excluding price, location, promotion, and service.